Insulin Resistance Indexes, Predictors of Diabetic Kidney Disease in Elderly Iraqis - Aldbagh, Mayyada Bassim Rasul (Technium BioChemMed, 2025)
This cross-sectional study aimed to evaluate the utility of three surrogate markers of insulin resistance, TyG, TG/HDL, and TyG-BMI in clinical practice by examining their association with diabetic kidney disease (DKD). Results: Of 476 patients with type 2 diabetes (T2DM), 42 (8.8%) had DKD. Patients with DKD showed significantly higher levels of BMI, fasting blood glucose, HbA1c, lipids, markers of renal dysfunction and three IR indices (TyG, TG/HDL and TyG-BMI) than those without DKD compared to those without DKD. Crosstabs/Risk analysis revealed that TyG index (OR = 1.39, 95% CI =1.218-1.587, p= 0.002), TG/HDL (OR =1.356, 1.189-1.545, p= 0.004), and TyG-BMI (OR =1.247, 1.073-1.450, p= 0.043). Based on the receiver operating characteristic curve, the areas under ROC with best cutoff values of TyG index, TG/HDL and TyG-BMI, were 0.762, 0.720 and 0.654, respectively and 9.5, 2.19 and 225, respectively. DKD patients >40 years had a significantly increased TyG index (p = 0.047) of 67.0% compared to patients <40 years of age of 50.0%. Conclusion: Among T2DM patients, the risk of DKD increases with the increase of TyG index, TG/HDL and TyG-BMI, with their respective cut-off values being 9.5, 2.19 and 225. The TyG performed best in predicting DKD, followed by TG/HDL and then TyG-BMI. Age was positively associated with TyG index, indicating a higher prevalence of DND in patients with T2DM.